An integrated study of the biodiversity within the Pseudechiniscus suillus–facettalis group (Heterotardigrada: Echiniscidae). Issue 3 (16th July 2019) - Cesari, Michele; Montanari, Martina; Kristensen, Reinhardt M; Bertolani, Roberto; Guidetti, Roberto; Rebecchi, Lorena
Abstract: Pseudechiniscus is the second most species-rich genus in Heterotardigrada and in the family Echiniscidae. However, previous studies have pointed out polyphyly and heterogeneity in this taxon. The recent erection of the genus Acanthechiniscus was another step in making Pseudechiniscus monophyletic, but species identification is still problematic. The present investigation aims at clarifying biodiversity and taxonomy of Pseudechiniscus taxa, with a special focus on species pertaining to the so-called ' suillus – facettalis group', by using an integrated approach of morphological and molecular investigations. The analysis of sequences from specimens sampled in Europe and Asia confirms the monophyly of the genus Pseudechiniscus . Inside the genus, two main evolutionary lineages are recognizable: the P . novaezeelandiae lineage and the P . suillus–facettalis group lineage. Inside the P . suillus–facettalis group, COI molecular data points out a very high variability between sampled localities, but in some cases also among specimens sampled in the same locality (up to 33.3% p-distance). The integrated approach to the study of Pseudechiniscus allows confirmation of its monophyly and highlights the relationships in the taxon, pointing to its global distribution.